Treatment and biologic maintenance-dosing patterns among pediatric patients with ulcerative colitis or Crohn's disease. (2nd January 2023) - Hunter, Theresa; Komocsar, Wendy J.; Colletti, Richard B.; Liu, Chunyan; Benkov, Keith J.; Dotson, Jennifer L.; Steiner, Steven J.; Zhang, Nanhua; Crandall, Wallace; ,
Abstract: Objectives: To assess treatment patterns and initial and maintenance dosing of biologics over 3 years in pediatric patients with ulcerative colitis (UC) or Crohn's disease (CD), utilizing data from the ImproveCareNow registry. Methods: Pediatric patients diagnosed with UC or CD and aged 2–17 years were included in the study. Descriptive statistics were employed to summarize baseline demographics. The proportion of patients on medication for UC or CD were analyzed at the baseline visit, 1-year, and 3-year time points (Cohort 1). Biologic maintenance dosage was calculated only for patients who had data for dose and weight at all-time points (Cohort 2). Results: In Cohort 1 (UC = 1784; CD = 4720), baseline treatment in UC included corticosteroid, 5-ASA, and 6-MP/AZA; at 1-year and 3-year time points, treatment with 5-ASA and corticosteroid decreased, whereas 6-MP/AZA and anti-TNFs increased. In CD, baseline treatment included corticosteroid, anti-TNF, 6-MP/AZA, and methotrexate; use of corticosteroids decreased, whereas the use of methotrexate and anti-TNFs increased over 3 years. In Cohort 2 (UC = 350; CD = 1537), at first maintenance dose, UC patients on infliximab received a mean dose of 10.5 mg/kg/8 wk, adalimumab (weight < 40 kg and ≥40 kg) 1.3 mg/kg/2 wk and 0.8 mg/kg/2 wk, and vedolizumab 6.9 mg/kg/8 wks. At the first maintenance dose, CD patients on infliximab received a mean dose of 8.1 mg/kg/8 wk, adalimumab (weight < 40 kg) 1.1 mg/kg/2 wk, adalimumab (weight ≥ 40 kg) 0.8 mg/kg/2 wk, and vedolizumab 10.5 mg/kg/8 wks. Conclusion: The use of corticosteroids was common at the initial visit in patients. Anti-TNFs remain the most used class of biologics, however, reported doses in our study were substantially higher than the standard dosing guidelines.